Occurrence of fungal diseases in vanilla (Vanilla planifolia andrews) in Kerala - Jithya Dhanesh, R Suseela Bhai (Journal of Spices and Aromatic Crops, 2008)
A study was carried out to evaluate the distribution and incidence of various fungal diseaseon vanilla (Vanilla planifolia Andrews ) in major vanilla growing tracts of Kerala. The studincluded both survey and assessment of diseases as and when reported by farmers. Survewas conducted during April, May and August 2003, March 2004 and November 2005. Atotal of 111 locations (72 locations during survey and 39 locations from farmer's reportsdistributed in six districts were subjected for the study. The major disease noticed in surveduring April -May 2003 was yellowing and premature bean shedding (YPBS). The diseaswas found associated with Colletotrichum vanillae Massae, predisposed by high temperaturand low relative humidity. During August 2003, Phytophthora incited stem and bean infectiowas noticed in isolated areas in Kozhikode and Idukki districts. Survey during March 200at Kozhikode revealed the recurrence of flower shedding and YPBS, besides root rot causedby Fusarium oxysporum f. sp. vanillae . Survey during November 2005 in Wyanad area revealedthe prevalence of stem and root rot incited by Fusarium species along with leaf axil rot incitedby Colletotrichum sp. In addition, Rhizoctonia solani, Cylindrocladium quinqueseptatum and Mucoracemosus were also isolated as pathogens from different symptomatic parts. Other minoinfections noticed were leaf rot, bean rot and brown rot. Fusarium and Colletotrichum sp. werthe predominant pathogens found to be associated with most of the infections on vanillaThe association of Mucor sp. with leaf and bean rot and C. quinqueseptatum with brown rowere observed as new reports of its kind on vanilla.